Identification, mapping and evolutionary course of wheat lipoxygenase-1 genes located on the A genomes - Garbus, Ingrid (2013)
Durum wheat (Triticum turgidum)is the cereal of preference for semolina and pasta production. Bright yellow color, which is desirable for pasta making, depends on the amount of carotenoid pigments present in the grain. Lipoxygenases (LPXs) account for most of the carotenoid degradation activity. Although B genome Lpx genes have been extensively described, little information about the A genome has been reported. Here, we demonstrate that the Lpx-A1 locus is represented by a single gene in the diploid T. urartu, the tetraploid T. turgidum and the hexaploid T. aestivum wheats in contrast to the multiple copies reported in B genome. The Lpx-A1_like pseudogene previously identified in T. turgidum genome A was also identified in the T. aestivum cv Chinese spring wheat, whereas T. urartu possesses a complete copy, suggesting that pseudogenization occurred after the formation of the tetraploid and then passes to the hexaploid wheat. The nucleotide sequence of T. urartu Lpx is more closely related to genome B Lpx-1 than to Lpx genes of genome A from T. turgidum and T. aestivum, probably due to the deletions and insertions occurred. Thus, the present paper extends our knowledge of lipoxygenase gene organization and evolution in the wheat A genome.